THE EFFECT OF UNSYSTEMATIC RISKS AND FINANCIAL FLEXIBILITY ON PROFITABILITY IN LOSER BANKS-A CASE STUDY FROM IRAQI BANKS - Majeed Mohsen Mohammad, PhD (Journal Park Publishing, 2023)
The research was aimed to find the effect of unsystematic risks and financial flexibility on profitability in loser banks in light of a bad distribution of risks and an inability to seize exceptional, rare and rapid opportunities in a highly changing environment are limiting profitability assuming To fulfill this aim, the data was from sample of 4 from total 13 Iraqi banks listed in the first market of Stock Exchange in Iraq, the research had comparing between the average return on assets for each bank for the period 2011-2020 with the risk-free rate, where the bank whose average return is less than the risk-free rate was classified in loser bank The research used the semi standard deviation and downside beta to find systematic risk, and unsystematic risks The multiple linear regression coefficient had used. The result that financial flexibility and unsystematic risks negatively effect on profitability which reflects inefficient in using financial resources and bad managing the risks.
Keywords: financial flexibility, unsystematic risk, profitability JEL Classification: G32.